PENGARUH KEMUDAHAN AKSES DAN KEAMANAN TERHADAP MINAT PENGGUNAAN APLIKASI DIGITAL PAYMENT SHOPEEPAY DIKALANGAN MAHASISWA - M. Mazidan; El-Munawwarah; Nurhikmah; Kholid Ansori (Jurnal Riset Multidisiplin Edukasi, 2025)
The rapid development of digital technology has significantly transformed payment systems, particularly through the use of digital payment services. ShopeePay is one of the most widely used digital wallet applications among university students due to its ease of access and security features. This study aims to examine the effect of ease of access and security on the intention to use the ShopeePay digital payment application among students of the Islamic Economics Study Program at Batang Hari Islamic University.This research employed a quantitative approach using a survey method. A total of 36 respondents were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS software.The results indicate that ease of access has a positive and significant effect on the intention to use ShopeePay. Similarly, security also has a positive and significant influence on usage intention. Simultaneously, ease of access and security significantly affect students’ intention to use the ShopeePay digital payment application. These findings suggest that improving accessibility and security can enhance users’ interest in adopting digital payment services.